Genome-Wide Association Identifies TBX5 as Candidate Gene for Osteochondrosis Providing a Functional Link to Cartilage Perfusion as Initial Factor - Rangkasenee, Noppawan; Muràni, Eduard; Brunner, Ronald M.; Schellander, Karl; Cinar, Ulas M.; Luther, Henning; Hofer, Andreas; Stoll, Monika; Witten, Anika; Ponsuksili, Siriluck; Wimmers, Klaus (Frontiers in Genetics, 2013)
Osteochondrosis (OC) is an orthopedic syndrome of the joints that occurs in children and adolescents and domestic animals, particularly pigs, horses, and dogs. OC is the most frequent cause of leg weakness in rapidly growing pigs causing animal welfare issues and economic losses. In this study, a genomewide association study (GWAS) was performed using the Porcine 60k SNPChip in animals of the breed Large White (n=298) to identify chromosome regions and candidate genes associated with OC lesion scores. A total of 19 SNPs on chromosomes (SSC) 3, 5, 8, 10, 14 and 18 were significantly associated with OC lesion scores (p-values ≤ 10-5). The SNPs MARC0098684, MARC00840086, MARC0093124 and ASGA0062794 at SSC14 36.1 to 38.2 Mb encompass a region of six linkage disequilibrium (LD) blocks. The most significant SNP ASGA0062794 is located in a LD block spanning 465 kb and covering the gene encoding T-box transcription factor 5 (TBX5). A SNP (c.54T>C) identified in TBX5 was significantly associated with OC lesions scores in a single marker analysis. TBX5 c.54T>C showed highest linkage disequilibrium with ASGA00627974 (r2=0.96) and superior association with OC lesion scores over other SNPs when included in the genome scan, whereas its treatment as an additional fixed effect in the GWAS statistical model led to a drop of significance of nearby markers. Moreover, real time PCR showed different transcript abundance of TBX5 in healthy and defect cartilage. The results imply that the association signal obtained on SCC14 is largely attributable to TBX5 c.54T>C likely to be in linkage disequilibrium with a regulatory polymorphism of TBX5. The transcription factor TBX5 interacts with GJA5 and MEF2C both being involved in vascularization. This study provides evidence for epistatic interaction of TBX5 and MEF2C, thus supporting deficiency of blood supply to growth cartilage as being fundamental for the initiation of osteochondrosis.